Cystic duct cyst (Revista Argentina de Cirugía, 2021)
Congenital biliary duct cysts are rare and are defined as cystic dilatations of the biliary tree in any of its portions. Cystic duct cysts are more uncommon. Their etiology remains uncertain and they should be resected due to the possible development of malignancy. We report the case of a female patient with a diagnosis of dilation of the cystic duct that was treated with laparoscopic surgery.
Keywords: congenital cyst; cystic duct; biliary